2020
DOI: 10.1038/s41598-020-61626-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different transcranial direct current stimulation protocols on visuo-spatial contextual learning formation: evidence of homeostatic regulatory mechanisms

Abstract: In the present study we tested the effects of different transcranial direct current stimulation (tDCS) protocols in the formation of visuo-spatial contextual learning (VSCL). The study comprised three experiments designed to evaluate tDCS-induced changes in VSCL measures collected during the execution of a visual search task widely used to examine statistical learning in the visuo-spatial domain. In Experiment 1, we probed for the effects of left-posterior parietal cortex (PPC) anodal-tDCS (AtDCS) at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Considering previous evidence which highlights the crucial role of timing in tDCS-learning interactions (Fricke et al, 2011;Pirulli et al, 2013;Roth-Alpermann et al, 2006), it is unlikely that the P2 increase and VSCL decrease that we observed are mere by-products of the stimulation alone, but rather reflect the interaction between offline 3 mA AtDCS induced effects and the following task-related cortical activation. This interpretation is supported by results obtained in our previous work where we showed that online (rather than offline) application of the same AtDCS protocol did not produce such a detrimental effect on behaviour (Grasso et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Considering previous evidence which highlights the crucial role of timing in tDCS-learning interactions (Fricke et al, 2011;Pirulli et al, 2013;Roth-Alpermann et al, 2006), it is unlikely that the P2 increase and VSCL decrease that we observed are mere by-products of the stimulation alone, but rather reflect the interaction between offline 3 mA AtDCS induced effects and the following task-related cortical activation. This interpretation is supported by results obtained in our previous work where we showed that online (rather than offline) application of the same AtDCS protocol did not produce such a detrimental effect on behaviour (Grasso et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, we appraised the neurophysiological effects caused by the interaction of AtDCS and VSCL. In a previous work we showed that 3 mA AtDCS applied on PPC before the execution of a VSCL paradigm reduced the participants' ability to learn visuo-spatial configurations of stimuli (Grasso et al, 2020). Behavioural data from the present study confirmed the AtDCSmediated reduction of VSCL.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, also our results suggest that numerosity adaptation likely affects cortical areas located within a relatively high hierarchical node while leaves activity within earlier cortical regions mostly unchanged. This is because while early component of the visual ERP response have been mostly associated with activity arising from striate or early extrastriate regions ( Di Russo et al, 2002 ), the P2p component was found to originate from the parietal cortex ( Hyde and Spelke, 2012 ; Fornaciai et al, 2017 ) and its amplitude was found to vary when low electrical current are applied over posterior parietal cortex ( Grasso et al, 2020b , 2021c ). Finally, we recently showed that numerosity adaptation is selective to salient features, such as color, suggesting that adaptation to numerical quantities likely occurs after feature-binding and other processing contributing to object recognition ( Grasso et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility for double blinding allows for a more rigorous evaluation of the after-effects induced by active stimulation (Gandiga and others 2006). Although the exact mechanism of action of tDCS is still debated, the current triggers a dynamic adaptation of the threshold potential, increasing the probability that the synaptic input will generate a response in output neurons (Grasso and others 2020; Orlov and others 2017a). Importantly, it has been shown that tDCS effects can persist beyond the period of stimulation (Kuo and others 2008; Nitsche and others 2003; Nitsche and Paulus 2000, 2001), and that such long-term effects are likely mediated by changes in N -methyl- d -aspartate (NMDA) and GABA receptors activity, resulting in modulation of neural plasticity (Kuo and others 2014) (Fig.…”
Section: Introductionmentioning
confidence: 99%